ICEBEAR: An All‐Digital Bistatic Coded Continuous‐Wave Radar for Studies of the E Region of the Ionosphere. Issue 4 (30th April 2019) - Huyghebaert, Devin; Hussey, Glenn; Vierinen, Juha; McWilliams, Kathryn; St‐Maurice, J.‐P.
Abstract: The Ionospheric Continuous‐wave E region Bistatic Experimental Auroral Radar (ICEBEAR) is a coherent scatter ionospheric radar. It operates at a frequency of 49.5 MHz, which is ideal for observing E region coherent echoes. The radar is located in Saskatchewan, Canada, and is operated by the University of Saskatchewan. The ICEBEAR system uses a continuous‐wave (CW) signal and requires isolation between the receiving and transmitting arrays. This was accomplished through a bistatic setup, where the receiver and transmitter are ≈240 km apart. Currently, the ICEBEAR system implements a pseudo random noise phase modulation on this CW signal to obtain 3‐km range resolution and 5‐s integration time images of E region ionospheric irregularities over a 600 km × 600 km field of view. The center of the field of view is located at ≈58°N, 106°W. The radar design allows for future improvements to temporal and/or spatial resolutions. Each site consists of a linear phased array with 10 equally spaced antennas. This, combined with modern digital radio hardware, provides azimuthal angle of arrival measurements at the receiving array and azimuthal transmission control at the transmitting array. This publication describes the radio hardware and signal processing used by the ICEBEAR radar and emphasizes the unique capabilities of the radar. First ICEBEAR observations from a Kp ≥ 4 event on 10 March 2018, are presented and shown to produce simultaneously the four types of previously characterized E region coherent scatter echoes. Key Points: A fully digital and remotely controlled radar installation named ICEBEAR with a bistatic setup is now operational ICEBEAR is the first continuous‐wave spread‐spectrum radar to measure ionospheric E region auroral irregularities ICEBEAR makes high spatiotemporal resolution images of auroral E region irregularities over a 600 km by 600 km field of view